2011
DOI: 10.1128/iai.01187-10
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirements for NAIP5 in Activation of the NLRC4 Inflammasome

Abstract: Inflammasomes are cytosolic multiprotein complexes that assemble in response to infectious or noxious stimuli and activate the CASPASE-1 protease. The inflammasome containing the nucleotide binding domainleucine-rich repeat (NBD-LRR) protein NLRC4 (interleukin-converting enzyme protease-activating factor [IPAF]) responds to the cytosolic presence of bacterial proteins such as flagellin or the inner rod component of bacterial type III secretion systems (e.g., Salmonella PrgJ). In some instances, such as infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 30 publications
7
94
0
8
Order By: Relevance
“…These data demonstrated that L94 was a critical residue for the engagement of the inflammasome via IPAF, in addition to residues present at the C terminus of the D0 domain of flagellin monomer (14,17,19). Alternatively, other Nod-like receptors such as Naip5 (19,20) may also be involved in the differential binding of flagellin L94.…”
Section: Discussionmentioning
confidence: 96%
“…These data demonstrated that L94 was a critical residue for the engagement of the inflammasome via IPAF, in addition to residues present at the C terminus of the D0 domain of flagellin monomer (14,17,19). Alternatively, other Nod-like receptors such as Naip5 (19,20) may also be involved in the differential binding of flagellin L94.…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with a role for IL-1 in the in vivo differentiation of Th17 cells during L. pneumophila infection, our results show compromised Th17 differentiation in the absence of MyD88, caspase-1, IL-1, and, to some extent, IPAF, indicating an important role for inflammasome activation and the subsequent secretion of IL-1 in the promotion of Th17 responses. L. pneumophila-derived flagellin was shown to activate cell surface TLR5 (46); however, it can also access the cytosol via L. pneumophila T4SS, where it activates the NLRs IPAF and Naip5 (35)(36)(37)47). Because both cytosolic PRRs were shown to activate caspase-1 and, thereby, induce the secretion of IL-1b (37,48), this likely explains the fact that Th17 responses were less impaired in the sole absence of IPAF compared with the absence of MyD88, caspase-1, or IL-1R.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the innate immune response to L. pneumophila demonstrated that inflammasome activation via recognition of L. pneumophila-derived flagellin plays a critical role in the secretion of IL-1b (35)(36)(37). It is well established that IL-1 has a strong influence on CD4 T cell differentiation, mainly toward the Th17 lineage (38-41).…”
Section: Il-1 and The Ipaf Inflammasome Promote Th17 Development In Vivomentioning
confidence: 99%
“…In its monomeric form it is recognized by two Pathogen Recognition Receptors (PRRs), TLR5 that senses extracellular FliC 16 and NLRC4/NAIP5 inflammasome that detects intracellular flagellin 17,18 . When FliC is sensed by the PRRs an important inflammatory response is triggered.…”
Section: Introductionmentioning
confidence: 99%